The fundamentals of workplace learning understanding how people learn in working life - Illeris, Knud (London Routledge, 2011)
A guide to how people learn in the workplace, and the issues and challenges involved. Examining the fundamental characteristics of workplace learning and unravelling the various influences which affect the success of learners in a work-based environment, it explains how diverse individuals can be encouraged and invited to learn at work.
Introduction -- How we learn -- The workplace as a learning space -- Workplace learning as a whole -- Workplace learning as competence development -- The workplace as a framework for learning -- Learning initiatives in connection with daily work -- Sparring and support schemes -- Job-transcending learning initiatives -- Interaction between workplace learning, courses and education -- The general conditions of workplace learning -- Special learner groups -- Some general conclusions.
Keywords: Organizational learning; Employees -- Education (Continuing education).; Adult learning; Work -- Psychological aspects